2016
DOI: 10.1002/vms3.39
|View full text |Cite
|
Sign up to set email alerts
|

The risk of carriage of Salmonella spp. and Listeria monocytogenes in food animals in dynamic populations

Abstract: Salmonella spp. and Listeria monocytogenes are foodborne pathogens of global importance. We assessed their risks and associated factors in a highly dynamic population of animals. Animal and environmental samples were collected from dairy cattle, sheep, camel and chickens at either the farms or the abattoirs. The pathogens were detected using a combination of bacterial enrichment culture and real‐time polymerase chain reaction (PCR). Data on putative risk factors were collect and analysed for their significance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
(42 reference statements)
0
7
1
Order By: Relevance
“…This finding is in contrast to previous reports indicating S. Typhimurium to be either the predominant (Kidanemariam et al, 2010;Molla et al, 2006;Moussa et al, 2012;Stipetic et al, 2016;Tadesse, 2015;Wani et al, 2013;Yang et al, 2014) or the second-most dominant (Lewerin et al, 2011;Tadesse and Tessema, 2014) serovar isolated. There are only a few reports that mention S. Newport as the second-most dominant serovar and one of the lesser isolated serovars in sheep FC (Dargatz et al, 2015;Stipetic et al, 2016;USDA, 2013). Additionally, parallel to our findings, S. Kentucky was indicated as the second-most predominant serovar by Dargatz et al (2015).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This finding is in contrast to previous reports indicating S. Typhimurium to be either the predominant (Kidanemariam et al, 2010;Molla et al, 2006;Moussa et al, 2012;Stipetic et al, 2016;Tadesse, 2015;Wani et al, 2013;Yang et al, 2014) or the second-most dominant (Lewerin et al, 2011;Tadesse and Tessema, 2014) serovar isolated. There are only a few reports that mention S. Newport as the second-most dominant serovar and one of the lesser isolated serovars in sheep FC (Dargatz et al, 2015;Stipetic et al, 2016;USDA, 2013). Additionally, parallel to our findings, S. Kentucky was indicated as the second-most predominant serovar by Dargatz et al (2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, there was less fecal contamination risk during evisceration due to the natural pellet form of sheep feces, which does not stick and smear to the carcass. Previous studies have indicated the absence (Kuma et al, 2017;Ranucci et al, 2014) or presence (Duffy et al, 2010;Stipetic et al, 2016;Tekelu and Negussie, 2011) of Salmonella in sheep carcasses. Differences observed in prevalence rates in these studies were reported to arise from the general hygiene status of slaughterhouses; whether slaughtering is applied in monorail conveyors or on the floor; sheep's initial pathogen carriage rate, increasing risk of shedding during transport stress leading to higher fecal contamination of carcass, and differences in sensitivity of Salmonella detection procedures.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A study performed in Uganda reported S. Newport, S. Guildford, S. Coleypark, S. Damman as frequent pig serotypes (26), previously described in humans. Osman et al (27), evidenced S. Haifa in duck embryos, this serotype has also been isolated from bovine feces (28), and humans (26), suggesting adaptation to different animal species. Additionally, S. London an unusual serotype was also identified.…”
Section: Resultsmentioning
confidence: 96%